Does the free trade zone promote green technological innovation?—evidence from the perspective of industrial agglomeration and digital economy in 285 cities in China - Zhang, Henan; Jia, Shangyue; Ren, Binyu; Ge, Hongling (Frontiers in Sustainable Cities, 2025)
This study aims to clarify the intrinsic relationship among the establishment of FTZs, industrial agglomeration, the digital economy, and green technological innovation. This paper empirically examines the impact of the establishment of FTZs on regional GTI and its mechanisms, based on panel data from 285 cities between 2009 and 2022, using the DID method. The findings show that the establishment of FTZs significantly enhances the level of GTI in the cities where they are located, with the GTI index increasing by an average of 696.501 units. Regional analysis reveals that coastal FTZs have a significantly stronger positive effect on GTI than inland and border FTZs. Furthermore, the promotion of GTI by FTZs intensifies with rising per capita GDP. Mechanism analysis indicates that FTZs promote the development of green industries through industrial agglomeration and the digital economy, thereby further stimulating GTI. Based on these findings, this paper proposes four policy recommendations: (1) strengthen region-specific policies and develop strategies to support GTI tailored to regional characteristics; (2) promote industrial transformation and upgrading, encouraging the green transformation of traditional industries; (3) improve the policy support system and optimize incentives for GTI; (4) enhance the greening of the financial system to increase the marketization and internationalization of green financial products.